Germline Compound Heterozygous Variants Identified in the STXBP2 Gene Leading to a Familial Hemophagocytic Lymphohistiocytosis Type 5: A Case Report - Dantas, Vera Maria; Valle, Cassandra Teixeira; de Oliveira, Roberta Piccin; Bezerra, Mylena Taíse Azevedo L.; do Amaral, Cleia Teixeira; Brandão, Raissa Anielle S.; Cerqueira Maia, Jussara M.; Petta, Tirzah Braz (Frontiers in Pediatrics, 2021)
Familial hemophagocytic lymphohistiocytosis (FHL) is a rare, potentially fatal autosomal recessive immunodeficiency, and STXBP2 mutations have been associated with FHL type 5 (FHL-5). Here, we report a case of a 2-year-old boy who presented with recurrent fever, hepatosplenomegaly, pancytopenia, hyperferritinemia, and hypofibrinogenemia since 4 months of age. His genetic analysis revealed a compound heterozygosity of the STXBP2 gene with a described pathogenic mutation c.1247-1G>C (splicing acceptor site) harbored by his father and a likely pathogenic variant of uncertain significance (VUS) c.704G>A (p.Arg235Gln) harbored by his mother. He was diagnosed as compound heterozygous for FHL-5 and was treated with the HLH-2004 protocol. Since treatment, this patient has been in remission, and he is being evaluated for a hematopoietic stem cell transplantation (HSCT).